Adverse events following vaccination with an inactivated, Vero cell culture-derived Japanese encephalitis vaccine in the United States, 2012–2016. Issue 29 (5th July 2018) - Walker, William L.; Hills, Susan L.; Miller, Elaine R.; Fischer, Marc; Rabe, Ingrid B.
Abstract: Background: In March 2009, the U.S. Food and Drug Administration licensed an inactivated Vero cell culture-derived Japanese encephalitis vaccine (JE-VC [IXIARO®]) for use in persons aged ≥17 years. In 2013, licensure was extended to include children aged ≥2 months. A previous analysis reviewed adverse events reported to the U.S. Vaccine Adverse Event Reporting System (VAERS) from May 2009 through April 2012. Methods: We reviewed adverse events reported to VAERS following JE-VC administered from May 1, 2012 through April 30, 2016. Adverse event reporting rates were calculated using 802, 229 doses distributed. Results: During the 4-year period, 119 adverse event reports were received for a reporting rate of 14.8 per 100, 000 doses distributed. Nine (8%) adverse events were classified as serious for a reporting rate of 1.1 per 100, 000 distributed. The most commonly reported event was hypersensitivity ( n  = 24; 20%) for a rate of 3.0 per 100, 000 doses distributed; 1 anaphylaxis event was reported. Ten (8%) neurologic events were reported for a rate of 1.2 per 100, 000 doses distributed; 2 events were classified as seizures. Sixty-three (53%) adverse events occurred after a first dose of JE-VC. Eighty (67%) adverse events occurred after administration of JE-VC with other vaccines. Eleven (9%) adverse events were reported in children; 1 was considered serious. Conclusions: These data continue to support the generally favorable safety profile of JE-VC. Reporting rates of adverse events were similar to those of the previous analysis. Although reporting rates of adverse events in children could not be calculated, there were low numbers of reported events in this age group. Post-licensure adverse event surveillance for this relatively new vaccine continues to be important to monitor adverse event reporting rates and identify possible rare serious events.